Intratracheally Administered Peptide-Modified Lipid Admixture Containing Fasudil and/or DETA NONOate Ameliorates Various Pathologies of Pulmonary Arterial Hypertension - Tanoy Sarkar; Sakib M. Moinuddin; Ayman Isbatan; Jiwang Chen; David Mann; Fakhrul Ahsan (MDPI AG, 2023)
This study examined the therapeutic potential of a combination therapy using fasudil, a Rho-kinase inhibitor, and DETA NONOate (DN), a nitric oxide donor, delivered as a lipid admixture modified with a cyclic homing peptide known as CAR (CAR-lipid mixture) for the treatment of pulmonary arterial hypertension (PAH). CAR-lipid mixtures were initially prepared via a thin-film hydration method and then combined with fasudil, DN, or a mixture of both. The therapeutic efficacy of this drug-laden lipid mixture was evaluated in a Sugen/Hypoxia (Su/Hx) rat model of PAH by measuring RV systolic pressure (RVSP), mean pulmonary arterial pressure (mPAP), Fulton indices, and assessing right ventricular (RV) functions, as well as evaluating pulmonary vascular morphology. Rats that received no treatment exhibited increases in RVSP, mPAP, Fulton indices, and changes in RV functional parameters. However, the treatment with the CAR-lipid mixture containing either fasudil or DN or a combination of both led to a decline in mPAP, RVSP, and Fulton indices compared to saline-treated rats. Similarly, rats that received these treatments showed concurrent improvement in various echocardiographic parameters such as pulmonary acceleration time (PAT), tricuspid annular plane systolic excursion (TAPSE), and ventricular free wall thickness (RVFWT). A significant decrease in the wall thickness of pulmonary arteries larger than 100 µm was observed with the combination therapy. The findings reveal that fasudil, DN, and their combination in a CAR-modified lipid mixture improved pulmonary hemodynamics, RV functions, and pathological alterations in the pulmonary vasculature. This study underscores the potential of combination therapy and targeted drug delivery in PAH treatment, laying the groundwork for future investigations into the optimization of these treatments, their long-term safety and efficacy, and the underlying mechanism of action of the proposed therapy.